Tunable Monopole Circular Microstrip Antenna for Dual frequency Covering L, C and X band Applications - Rajendra, Biradar; Mulgi, S. N. (International Journal of Computer Sciences and Engineering, 2019)
In this paper, we have presented simulated and measured results of tunable monopole circular microstrip antenna for dual frequency which covers L, C, and X band applications. The proposed antenna consists of two identical stubs placed along the patch axis having fixed width WS =1.0 cm. The slot is placed on left side of feed axis which is having fixed L1= 1.279 cm, L2 =1.3 cm and width W1= 0.1 cm. The upper and lower length of two identical stub is varied from LUS=0.483 to 1.83 cm and LLS=0.257 to 0.957 cm to tune an antenna for dual band. The first band varies from 1.8325 GHz to 1.5175 GHz having tuning range of 17.48% and 16.0% and second band varies from 8.5375 GHz to 7.2775 GHz having tuning range of 14.77% and 12.48% when simulated and measured respectively. The maximum impedance bandwidth of 111 % and 30.9 % is achieved for first and second band respectively. The antenna has peak gain of 3.0 dB. The VSWR is less 2 than for all tuned frequencies. The proposed antenna covers applications of L, C and X band. The simulated results are in good agreement with experimental results. The radiation patterns are nearly omni-directional nature both in E and H plane.